2021
DOI: 10.3389/fcell.2021.642494
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes and Cancer Progression: A Malignant Liaison

Abstract: During primary tumorigenesis isolated cancer cells may undergo genetic or epigenetic changes that render them responsive to additional intrinsic or extrinsic cues, so that they enter a transitional state and eventually acquire an aggressive, metastatic phenotype. Among these changes is the alteration of the cell metabolic/catabolic machinery that creates the most permissive conditions for invasion, dissemination, and survival. The lysosomal system has emerged as a crucial player in this malignant transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 181 publications
2
48
0
Order By: Relevance
“…Drugs that diffuse into the cytoplasm are trapped in lysosomes and are rapidly effluxed by cancer cells that express multidrug resistance transporters. Doxorubicin, cisplatin, vincristine, vinblastine, sorafenib, and sunitinib are some examples of lysosomotropic chemotherapeutics [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Drugs that diffuse into the cytoplasm are trapped in lysosomes and are rapidly effluxed by cancer cells that express multidrug resistance transporters. Doxorubicin, cisplatin, vincristine, vinblastine, sorafenib, and sunitinib are some examples of lysosomotropic chemotherapeutics [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomes have recently emerged as important players in cancer development or progression, while targeting their function has been proposed as a promising strategy in cancer treatment (Machado et al, 2021;Tang et al, 2020). Recently, we showed that components of the ESCRT machinery could serve as potential therapeutic targets against colorectal cancer (CRC) (Kolmus et al, 2021;Szymanska et al, 2020), but whether modulation of ESCRT activity would affect lysosomal function in CRC cells has not been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, whether ESCRTs are implicated in the physiological regulation of lysosomal morphology, function or signaling in the absence of induced lysosomal damage has not been thoroughly addressed. This question is important for human health, as lysosomal function and signaling contribute to development or progression of cancer (Machado et al, 2021;Tang et al, 2020), including colorectal cancer (CRC) in which ESCRT machinery has been proposed as a promising therapeutic target (Kolmus et al, 2021;Szymanska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the acidic organelle in cells, the lysosome, as a proton store, is the center responsible for degradation, nutrient sensing and immunity [ 18 ]. At the same time, lysosomes are also closely related to the growth, proliferation and migration of tumor cells [ 19 ]. Targeting lysosomes to achieve H + -mediated ion interference therapy is also an effective means to treat cancers.…”
Section: Ion Interference Therapymentioning
confidence: 99%